The Urgency of Due Diligence in Minimizing Legal Risks in the International Pre-Contractual Stage - R. Odityo Valen Aprian Jaya; Wafda Vivid Izziyana (PT Justitia Legal Research, 2026)
This research aims to analyze the urgency of Due Diligence as a legal risk mitigation instrument in the pre-contractual stage of international business transactions. Cross-jurisdictional complexities often create information asymmetry leading to commercial disputes. The research method used is normative juridical with statutory and case approaches to examine the application of the precautionary principle. The results show that the majority of cross-border disputes are caused by failures to verify legal capacity, asset status, and regulatory compliance of foreign partners. The discussion emphasizes that Due Diligence findings must be concretely integrated into contract clauses, specifically Representations and Warranties. The conclusion asserts that Due Diligence is an absolute prerequisite (sine qua non) to ensure the validity of the agreement's subject and object, as well as to protect parties from potential financial losses and extraterritorial legal sanctions before the final agreement is signed.